Persekongkolan Tender Pengadaan Pekerjaan Pembangunan Gedung Kolam Renang Tahap II Kecamatan Kandangan Kabupaten Hulu Sungai Selatan - Salsabila Tamami; Galuh Puspaningrum (Journal of Private and Economic Law, 2022)
The definition of unfair business competition can be seen in Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition, namely competition between trade participants in the production and/or marketing of goods and/or services that is dishonest or violates the law. One example of a tender conspiracy case is the tender conspiracy for the Phase II Swimming Pool Construction Procurement, Kandangan District, Hulu Sungai Selatan Regency. Based on this case example, the author is interested in studying this case in depth and drawing out three problem formulations, including the Procurement of Phase II Swimming Pool Construction Work, Kandangan District, Hulu Sungai Selatan Regency, fulfilling the elements of conspiracy. Legal Considerations The KPPU's Decision Number 05/KPPU-I/2020 is in accordance with Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. Legal Consequences of KPPU's Decision Number 05/KPPU-I/2020 on Tender Participants. The type of research used by the researcher in this thesis is a type of normative juridical law research based on the analysis of norms and legal rules. And the research approach used by the author in this thesis is the legal approach and the conceptual approach. This journal discusses the first, namely the conspiracy that occurred in the tender for the Procurement of the Phase II Swimming Pool Building, Kandangan District, Hulu Sungai Selatan Regency. The second is regarding the legal considerations given by the Commission Council regarding the tender conspiracy for the Phase II Swimming Pool Construction, Kandangan District, Hulu Sungai Selatan Regency. And the third is regarding the legal consequences of the tender conspiracy for the Procurement of Phase II of the Swimming Pool Building, Kandangan District, Hulu Sungai Selatan Regency.